2006
DOI: 10.1103/physrevd.74.094005
|View full text |Cite
|
Sign up to set email alerts
|

Scalar glueball, scalar quarkonia, and their mixing

Abstract: The isosinglet scalar mesons f 0 (1710), f 0 (1500), f 0 (1370) and their mixing are studied. We employ two recent lattice results as the starting point; one is the isovector scalar meson a 0 (1450) which displays an unusual property of being nearly independent of quark mass for quark masses smaller than that of the strange, and the other is the scalar glueball mass at 1710 MeV in the quenched approximation. In the SU(3) symmetry limit, f 0 (1500) turns out to be a pure SU(3) octet and is degenerate with a 0 (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
166
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(175 citation statements)
references
References 59 publications
(74 reference statements)
8
166
1
Order By: Relevance
“…Thus, in this approach [2], there is only an small mixing between the singlet and the glueball. Using these values the prediction for B → f 0 (1500)K is in conflict with the experimental data.…”
Section: Branching Ratios and Mixingmentioning
confidence: 98%
See 3 more Smart Citations
“…Thus, in this approach [2], there is only an small mixing between the singlet and the glueball. Using these values the prediction for B → f 0 (1500)K is in conflict with the experimental data.…”
Section: Branching Ratios and Mixingmentioning
confidence: 98%
“…The values reported for the widths marked with * include the corresponding branching of the scalar decaying channel. To obtain the NFA predictions we used B(f0(1370) → 2π) = 0.26(1), B(f0(1500) → 2π) = 0.35 (2) and for the a0(1450) → πη no reliable value exists [3].…”
Section: Branching Ratios and Mixingmentioning
confidence: 99%
See 2 more Smart Citations
“…The fit to all decays showed the existence of two solutions, one in which f 0 (1500) is predominantly a glueball, and on in which f 0 (1710) is such. Shortly after, Cheng et al [28] also found a phenomenological solution in which f 0 (1710) is predominantly a glueball. Various other studies were performed which involved constituents quarks and gluons, e.g.…”
Section: Scalar Glueballmentioning
confidence: 97%